Zinc and Phosphorus Nutrition of Wheat Grown on a Highly Calcareous Soil - Damodar, D; Yadav, B R (Annals of Arid Zone, 2016)
A pot culture experiment was conducted to study the effect of different levels of P(O, 25, 50.and 100ppm) and Zn (0, 5, 10and ZO ppm) on their concentration and uptake by wheat biomass in a highly calcareous soil. P application decreased the concentration but increased the uptake of Zn in grain and straw parts of the plant. Zn availability in soil after crop harvest was also enhanced with application. However, Zn application did not affect either P concentration in the plant or in the soil significantly.